2020
DOI: 10.1111/aor.13775
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic extracellular matrix and platelet‐rich plasma constructing injectable hydrogel for pancreas tissue engineering

Abstract: The development of pancreatic extracellular matrices enriched with insulin-secreting β-cells is a promising tissue engineering approach to treat type 1 diabetes. However, its long-term therapeutic efficacy is restricted by the defensive mechanism of host immune response and the lack of developed vascularization as appropriate after transplantation. Platelet-rich plasma (PRP), as an autologous platelet concentrate, contains a large number of active factors that are essential for the cell viability, vascularizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…A positive effect on the number of β-cells was also observed when PRP was added during the differentiation of induced pluripotent stem cells [ 63 ]. When PRP was used in combination with biomaterials, specifically alginate and decellularized pancreatic extracellular matrix (dECM), this resulted in an improved viability, a higher insulin gene expression, and a higher insulin release from β-cell lines [ 64 , 65 ]. In the present study, we used platelet lysate produced from PRP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive effect on the number of β-cells was also observed when PRP was added during the differentiation of induced pluripotent stem cells [ 63 ]. When PRP was used in combination with biomaterials, specifically alginate and decellularized pancreatic extracellular matrix (dECM), this resulted in an improved viability, a higher insulin gene expression, and a higher insulin release from β-cell lines [ 64 , 65 ]. In the present study, we used platelet lysate produced from PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only supplementation with FFP resulted in fewer apoptotic nuclei from day 7 onwards and a higher proliferation until day 7. In contrast to this, in vitro other groups observed a definitive increase in the viability of murine islets after the addition of serum albumin to alginate [ 39 ], an increased viability of β-cell lines when PRP was added to alginate [ 64 ] or to pancreatic dECM [ 65 ], and an increased viability of murine islets when PRP was added to the culture medium [ 59 ]. Of these, only the study by Schneider et al with albumin-supplemented alginate analysed a time frame of more than one week [ 39 ], whereas the effect seen in the in vitro studies with PRP [ 59 , 64 , 65 ] was reported for a maximum of 5 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uteri from healthy sows were processed as we previously described ( López-Martínez et al , 2021a ), to produce the EndoECM, in accordance with ISO 9001 quality management, in relation to the safe and legal procurement of animal organs from the slaughterhouse. Then, as established in other studies using extracellular matrix hydrogels ( Zhang et al , 2020a ), 15% (v/v) of thawed hUC-PRP was supplemented in 6 mg/ml of EndoECM to prepare the EndoECM + hUC-PRP treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, using 3D culture in stem cell biology increases cell-cell and cell-matrix interactions and enables cell signaling by emulating in vivo environment. 14 In addition, 3D nanofibers can provide direct interaction with diverse ECM components such as biomolecules, molecular signaling, and growth factors. 15,16 Hence, 3D culture ameliorates the differentiation of diverse kinds of cells into IPCs compared to those differentiated in 2D culture.…”
Section: Introductionmentioning
confidence: 99%